Connecting the dots: History teaching in the 21st Century classroom – juggling reason, technology and multi-media in the world of the young technophile (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This article will focus on harnessing the latest in multi-media and technological gadgetry in the modern history classroom. Teenagers find themselves at the cutting edge of the world of “bits and bytes”, social media and a global network of knowledge. It is at that point that the history teacher needs to meet them and help them to engage with the past. A new horizon has opened up for the modern history teacher who, as a student of change can pass on the skills of change management. Looking into the past, the dots can be connected and scenario planning for the future can begin. In the history classroom, which is by its very nature interdisciplinary (because history is all about the story of what people do), various fields of study and kinds of reasoning meet. The modern history classroom should be relevant to teenagers navigating their way through a rapidly changing world which has been shrunk by technology and in which there has been an explosion of knowledge. It is the history teacher who can put that knowledge to work, if he/she meets the teenager at the intersection of technology and of the past. Knowledge alone is of little use if not tempered by wisdom, and it is the historian who can apply “reason” to snippets of information. In the 21st Century the history teacher must perform a delicate balancing act: reason, technology and the multi-media world of the young technophile must be juggled with consummate skill.
Keywords: Wireless router; Bluetooth; Netbook; Tablet; Kindle; Clean Slate